Forced KLF4 expression increases the generation of mature plasma cells and uncovers a network linked with plasma cell stage - Schoenhals, Matthieu; Jourdan, Michel; Seckinger, Anja; Pantesco, Véronique; Hose, Dirk; Kassambara, Alboukadel; Moreaux, Jérôme; Klein, Bernard (Cell cycle, 2016)
A role of the transcription factor Krüppel-like factor 4 (KLF4) in the generation of mature plasma cells (PC) is unknown. Indeed, KLF4 is critical in controlling the differentiation of various cell linages, particularly monocytes and epithelial cells. KLF4 is expressed at low levels in pro-B cells and its expression increases as they mature into pre-B cells, resting naïve B cells and memory B cells. We show here that KLF4 is expressed in human bone marrow plasma cells and its function was studied using an in vitro model of differentiation of memory B cells into long lived plasma cells. KLF4 is rapidly lost when memory B cells differentiate into highly cell cycling plasmablasts, poorly cycling early plasma cells and then quiescent long-lived plasma cells. A forced expression of KLF4 in plasmablasts enhances the yield of their differentiation into early plasma cell and long lived plasma cells, by inhibiting apoptosis and upregulating previously unknown plasma cell pathways.
Gesehen am 20.05.2020